Arabic Language Program Management at Al-Izzah Leadership School Batu Islamic Boarding School - Fasich Nur Firdaus; Ahmad Fuad Abdul Baqi; Ahmad Syaifuddin Romli (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2026)
This study examines the management of the Arabic language learning program at Al-Izzah Leadership School Islamic Boarding School, Batu, focusing on the core managerial functions of planning, organizing, implementation, and evaluation. Employing a qualitative case study approach, data were collected through observations, semi-structured interviews, and document analysis, and analyzed using data condensation, data display, and conclusion drawing. The findings reveal that program planning is systematically structured through short-, medium-, and long-term activities and is aligned with the Muadalah Madinah curriculum and Islamic studies framework. Organizationally, the program is supported by a clear division of roles involving school leaders, language coordinators, teachers, and student organizations, which facilitates effective coordination and language discipline. Program implementation integrates formal classroom instruction with contextual language habituation through daily, weekly, and annual activities that promote active Arabic use. Evaluation is conducted continuously through formative and summative assessments, encompassing daily language monitoring, weekly skill reinforcement, and semester-based competency testing. This study contributes to the field of Arabic language education management by presenting an integrative and context-based program management model within an Islamic boarding school setting. The novelty of this research lies in its documentation of Arabic language program management grounded in an internationally recognized curriculum and sustained language cultivation practices, which remain underexplored in existing studies. Abstrak Penelitian ini mengkaji manajemen program pembelajaran bahasa Arab di Pondok Pesantren Al-Izzah Leadership School Batu dengan menitikberatkan pada fungsi manajerial utama, yaitu perencanaan, pengorganisasian, pelaksanaan, dan evaluasi. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui observasi, wawancara semi-terstruktur, dan dokumentasi, kemudian dianalisis menggunakan tahapan kondensasi data, penyajian data, serta penarikan dan verifikasi kesimpulan. Hasil penelitian menunjukkan bahwa perencanaan program pembelajaran bahasa Arab disusun secara sistematis dalam kerangka kegiatan harian, mingguan, dan tahunan, serta selaras dengan kurikulum Muadalah Madinah dan kerangka studi keislaman. Dari aspek pengorganisasian, program didukung oleh pembagian peran yang jelas antara pimpinan pesantren, koordinator bahasa, guru, dan organisasi santri, sehingga tercipta koordinasi yang efektif dan disiplin berbahasa. Pelaksanaan program mengintegrasikan pembelajaran formal di kelas dengan pembiasaan bahasa secara kontekstual melalui berbagai aktivitas kebahasaan yang mendorong penggunaan bahasa Arab secara aktif. Evaluasi dilakukan secara berkelanjutan melalui penilaian formatif dan sumatif, mencakup pemantauan harian penggunaan bahasa, penguatan keterampilan mingguan, serta pengujian kompetensi pada akhir semester. Penelitian ini berkontribusi pada pengembangan kajian manajemen pendidikan bahasa Arab dengan menyajikan model pengelolaan program yang integratif dan berbasis konteks pesantren. Kebaruan penelitian ini terletak pada pengungkapan praktik manajemen pembelajaran bahasa Arab yang berlandaskan kurikulum berstandar internasional dan pembudayaan bahasa yang berkelanjutan, yang masih jarang dikaji secara mendalam.